1980
DOI: 10.1063/1.439106
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectroscopy of AgCl, AgBr, and AgI vapors

Abstract: He I photoelectron spectra of AgCl, AgBr and AgI vapors have been obtained which differ significantly from earlier work. In each instance, the characteristic features of the diatomic molecule are prominent. The spectral features separate into a valence region, predominantly halogen p-like, and a deeper region, predominantly of Ag 4d character. The latter is split by spin–orbit and ligand field interactions, which are parametrized from the experimental data. Relativistic calculations of the Xα–DVM–SCC type have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 23 publications
4
18
1
Order By: Relevance
“…The vapor of cuprous halides CuCl, CuBr, CuI contains mainly trimers but also tetramers [1][2][3][4], whereas monomers and dimers are roughly equally abundant in the vapors of AgCl, AgBr and AgI [5]. It has also been demonstrated that the trimer is a building block in silver hydroxide clusters [6][7][8].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The vapor of cuprous halides CuCl, CuBr, CuI contains mainly trimers but also tetramers [1][2][3][4], whereas monomers and dimers are roughly equally abundant in the vapors of AgCl, AgBr and AgI [5]. It has also been demonstrated that the trimer is a building block in silver hydroxide clusters [6][7][8].…”
Section: Introductionmentioning
confidence: 96%
“…The trimer is known to play a special role in noble metal halides in the gas phase: an amazing common property of all these compounds is the unusual abundance of trimers in their vapor [1][2][3][4][5]. The vapor of cuprous halides CuCl, CuBr, CuI contains mainly trimers but also tetramers [1][2][3][4], whereas monomers and dimers are roughly equally abundant in the vapors of AgCl, AgBr and AgI [5].…”
Section: Introductionmentioning
confidence: 98%
“…The nature of bondings (covalent or ionic) is still controversial. In gas phase, an amazing common property of all these compounds is the unusual abundance of trimers in their vapor [4][5][6][7][8][9][10][11][12], although smaller molecules like monomers, and eventually dimers are expected for metal halides. The relative large stability of the trimer was also shown in experiments of fragmentation of metastable clusters in the case of silver bromide [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The nature of bondings (covalent or ionic) is still controversial. In gas phase, an amazing common property of all these compounds is the unusual abundance of trimers in their vapor,[4–12] and even tetramer in the case of CuCl vapor,[13] although smaller molecules such as monomers, and eventually dimers are expected for metal halides. Very early, Schomaker and coworkers proposed a six‐membered alternating ring model to describe the structure of the cuprous chlorides trimer Cu 3 Cl 3 .…”
Section: Introductionmentioning
confidence: 99%